Navigating the Marketing Landscape: Strategies for Promoting Private Higher Education Institutions in South Africa - Swart, Emetia; Schutte, Flip (International Review of Management and Marketing, 2024)
Private institutions in South Africa’s higher education sector need effective marketing strategies to attract and retain students amidst competition. This article provides marketing strategies for Private Higher Education Institutions (PHEIs) in South Africa to navigate a competitive landscape. The objective of the research is to determine the effective media and marketing activities for PHEIs to target a larger market share. The study involved 23 semi-structured interviews with students enrolled at three PHEIs in South Africa. The researcher conducted a thematic analysis to identify patterns from transcribed interviews. Codes were created for each theme, and similar topics were clustered. Microsoft Word and Excel were used for data interpretation and visualisation. ATLAS.ti 22, a CAQDAS software, was employed for further analysis and interpretation. The study suggests that PHEIs in South Africa should prioritise their online presence, websites, and participation in high schools and career fairs to target a larger market share. Marketers should create and adapt their marketing strategies to include various communication channels and methods. Positive word-of-mouth interactions also play a significant role in the marketing efforts of PHEIs, so marketers should focus on developing strategies that generate such interactions.